2013
DOI: 10.3399/bjgp13x669149
|View full text |Cite
|
Sign up to set email alerts
|

Expectations for consultations and antibiotics for respiratory tract infection in primary care: the RTI clinical iceberg

Abstract: Qualitative interview study A sample of adult members of the public with diverse ethnicity and deprivation were opportunistically recruited in pharmacies in four areas of England. Responders who had recently had an RTI, were asked to participate in a later telephone interview.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
160
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(177 citation statements)
references
References 21 publications
15
160
1
1
Order By: Relevance
“…In previous studies in Western and Asian populations, patients have been observed to have a variable knowledge about the role of antibiotics in the common cold and cough, 30,31 and those with a suboptimal knowledge of antibiotics tended to request antibiotics from their GPs. Patients who requested antibiotics were more likely to have them prescribed.…”
Section: Discuss This Articlementioning
confidence: 99%
“…In previous studies in Western and Asian populations, patients have been observed to have a variable knowledge about the role of antibiotics in the common cold and cough, 30,31 and those with a suboptimal knowledge of antibiotics tended to request antibiotics from their GPs. Patients who requested antibiotics were more likely to have them prescribed.…”
Section: Discuss This Articlementioning
confidence: 99%
“…This is of interest since previous studies have shown that medical practitioners are confronted with demands for antibiotics from patients [25][26][27][28]. Time restrictions and high demand from patients jointly influence prescribers to prescribe antibiotics, even in cases where this might not be necessary in order to treat the infection.…”
Section: Previous Researchmentioning
confidence: 99%
“…Time restrictions and high demand from patients jointly influence prescribers to prescribe antibiotics, even in cases where this might not be necessary in order to treat the infection. In a study in the UK, it was found that about 96% of all patients who request antibiotics also receive it, indicating that antibiotic consumption might involve a shared decision-making between doctors and patients [25].…”
Section: Previous Researchmentioning
confidence: 99%
“…К сожалению, пока пропаганда более рационального антибактериального подхода приносит достаточно скромные результаты. Так, в опубликованном в 2013 г. опросе 1 767 взрослых паци-ентов в Англии с острыми инфекциями дыхательных путей (ОИДП) выяснилось, что 24% считают, что антибио-тики эффективно помогают при кашле и простуде, 38% считают, что антибиотики могут убить вирусы, 32% респон-дентов ожидают, что их врач общей практики пропишет антибиотики при симптомах гриппа, 17% -при боли в горле, 13% -от кашля, 6% -от простуды и 4% -от насморка [11].…”
unclassified